2015
DOI: 10.1016/j.ijimpeng.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic interface model for masonry walls subjected to high strain rate out-of-plane loads

Abstract: The present study proposes a dynamic constitutive material interface model that includes non-associated flow rule and high strain rate effects, implemented in the finite element code ABAQUS as a user subroutine. First, the model capability is validated with numerical simulations of unreinforced block work masonry walls subjected to low velocity impact. The results obtained are compared with field test data and good agreement is found. Subsequently, a comprehensive parametric analysis is accomplished with diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 12 publications
(24 reference statements)
0
19
0
Order By: Relevance
“…Conversely, both the present and the micro-model by Rafsanjami et. al [32] are accurate in predicting the peak displacement, with a relative error of around 10%. Fig.…”
Section: Numerical Model Validationmentioning
confidence: 97%
See 3 more Smart Citations
“…Conversely, both the present and the micro-model by Rafsanjami et. al [32] are accurate in predicting the peak displacement, with a relative error of around 10%. Fig.…”
Section: Numerical Model Validationmentioning
confidence: 97%
“…The wall is subjected to a low velocity impact load that tries to represent the impact of a vehicle. The comparisons will be performed by means of the experimental determined data [31], but also with numerical results collected from the studies of [25,32]. The selected parapets (from 21 tested) are designated as C6 and C7 and are replicates, see Fig.…”
Section: Numerical Model Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors [6,8,12,13] have identified the need for continuing development of these numerical modelling approaches to appropriately consider the variability present in masonry construction and its non-linear behaviour to give the most accurate predictions [3].…”
Section: Current Modelling Approaches For Dynamic And/or Out-of-planementioning
confidence: 99%